2016
DOI: 10.1080/21568235.2016.1154477
|View full text |Cite
|
Sign up to set email alerts
|

On the development of students’ attitudes towards corruption and cheating in Russian universities

Abstract: Based on empirical data from selected public universities in Khabarovsk, Russia, this paper compares first-and fifth-year students regarding their attitudes towards corruption in general and university corruption in particular. Even after making both groups of students comparable with respect to a range of socioeconomic characteristics by a matching approach, the results suggest that fifth-year students are more open to a range of informal and corrupt practices than first years. Our analysis therefore points t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0
4

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(17 citation statements)
references
References 28 publications
0
11
0
4
Order By: Relevance
“…There are studies devoted to the dynamics of attitudes towards academic cheating of students in the process of studying at a university. For example, Denisova-Schmidt et al (2016) compared the attitudes of first and fifth year students towards corruption in general and university corruption in particular (empirical data were obtained on the basis of individual state universities in Khabarovsk). The results showed that fifth-year students are more open to various informal and corrupt practices than freshmen.…”
Section: Problem Statementmentioning
confidence: 99%
“…There are studies devoted to the dynamics of attitudes towards academic cheating of students in the process of studying at a university. For example, Denisova-Schmidt et al (2016) compared the attitudes of first and fifth year students towards corruption in general and university corruption in particular (empirical data were obtained on the basis of individual state universities in Khabarovsk). The results showed that fifth-year students are more open to various informal and corrupt practices than freshmen.…”
Section: Problem Statementmentioning
confidence: 99%
“…A variety of factors are proposed by researchers to explain the high incidence of academic dishonesty Studies show that a lot of students consider academic dishonesty to be an acceptable and justified educational strategy [Lupton, Chapman 2002;Poltorak 1995;Denisova-Schmidt, Huber, Leontyeva 2016], which may stem from school experiences [Latova, Latov 2007] and overall tolerance of corrupt practices in Russia [Magnus et al 2002;Denisova-Schmidt 2017;2018]. Some researchers believe that academic dishonesty in Russian higher education may be aggravated by certain peculiarities of the system [Magnus et al 2002;Denisova-Schmidt, Huber, Leontyeva 2016;Leontyeva 2010], such as the funding model that makes it unprofitable for colleges to dismiss students for academic dishonesty [Denisova-Schmidt 2017;Golunov 2013]. Scholars also emphasize insufficiency of the anti-fraud policies implemented by universities and faculty [Shmeleva 2016;Golunov 2013].…”
Section: Doi: 1017323/1814-9545-2019-3-101-129mentioning
confidence: 99%
“…Senior students of Russian colleges are more tolerant to academic dishonesty than freshmen [Chirikov, Shmeleva 2018;Denisova-Schmidt, Huber, Leontyeva 2016]. It may be suggested that students tend to engage in corrupt practices more and more often as they progress through college.…”
Section: Contextual Factors Are Morementioning
confidence: 99%
“…Another study involv- ing students in economics and management programs of eight Russian universities found that one in six students believe that most exams and tests at their university can be passed by cheating, and over one third are convinced that many of their peers buy papers online [Maloshonok 2016]. A variety of factors are proposed by researchers to explain the high incidence of academic dishonesty Studies show that a lot of students consider academic dishonesty to be an acceptable and justified educational strategy [Lupton, Chapman 2002;Poltorak 1995;Denisova-Schmidt, Huber, Leontyeva 2016], which may stem from school experiences [Latova, Latov 2007] and overall tolerance of corrupt practices in Russia [Magnus et al 2002;Denisova-Schmidt 2017;. Some researchers believe that academic dishonesty in Russian higher education may be aggravated by certain peculiarities of the system [Magnus et al 2002;Denisova-Schmidt, Huber, Leontyeva 2016;Leontyeva 2010], such as the funding model that makes it unprofitable for colleges to dismiss students for academic dishonesty [Denisova-Schmidt 2017; Golunov 2013].…”
Section: Doi: 1017323/1814-9545-2019-3-101-129mentioning
confidence: 99%